Study of antimetastatic effects of antioxidants using caspase-3 sensor call lines - Lim, Mark Wen Lin (2016)
Cancer is presently one of the most deadly diseases in the world and new treatment or prevention methods are the subjects of constant research. Metastatic cancers are of particular importance, since majority of cancer deaths involve secondary tumours. Due to its interaction with reactive oxygen species, some antioxidants have been shown to have anti-cancer and anti-metastatic properties, however research so far has been inconclusive. This study screens antioxidants for anti-metastatic effects, utilizing a caspase-3 based biosensor that can accurately detect apoptosis. Metastatic human breast cancer cells MDA-MB-231 and metastatic melanoma cells B16-F10 were selected for this study and were transfected with the fluorescence resonance energy transfer (FRET)-based biosensor. The cells were then treated with 6 different antioxidants: β-carotene, Curcumin, Quercetin, Silymarin, Vitamins C (L- ascorbic acid) and Vitamin E (α-Tocopherol acetate), based on previous studies involving cancer and antioxidants. Varying concentrations used were adapted from these previous studies and the cell treatment was also carried out using three different incubation times. These cells were then tested for cell viability using the MTT cytotoxicity assay and anti- proliferative effects were further visualized using the caspase-3 biosensor. Vitamin C, Curcumin and Silymarin were shown to inhibit the proliferation of the metastatic cancer cell lines, while β-carotene, Quercetin and Vitamin E produced no significant positive outcomes. Two major protein pathways, phosphorylated-AKT and phosphorylated-ERK were tested on cells treated with the three effective antioxidants.